Perancangan Aplikasi E-Commerce Dengan Sistem Rekomendasi Item-Based Collaborative Filltering - Rio Oktora; Wiwin Susanty (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2013)
PD Damai Motors is one company in the town of Bandar Lampung engaged in the sale of spare parts, however, the system is running right now, there are still many problems that occur both on the vendor and on the part of consumers, especially outside the city of Bandar Lampung. The vendor has not had a special media to promote a product - products and recording sales transactions reports are done manually using only existing proof of the transaction. And consumers still have to directly come to the store if you want to get information about products and want to order the products according to the desired design, as well as the consumer should contact the vendor via sms / call if you want to know the progress of the production order. Scientific report will describe and explain the design Application E-Commerce system with Item-Based Collaborative Filltering clearly so that can know the location of the problem. In analyzing the system, the authors use analytical tools such as Document Flow Diagram (flowchart) and Unified Modeling Language (UML)XV + 60 + Attachment Refrences